Conserving Biodiversity: An Important Environmental Priority - DAVAR, MONIKA (SCHOOL SCIENCE, 2006)
BIODIVERSITY refers to variety and variability among living organisms, their genetic differences and the ecosystems in which they live. The distribution of living organisms is uneven on the earth because of different environmental conditions. Countries like Brazil, Columbia, Mexico, Indonesia, Peru, Malaysia, Ecuador, India, Zaire, Madagascar and Australia are known as mega diversity countries because of their rich biodiversity. India alone is estimated to have over 45,000 plants and 65,000 animal species. Biodiversity as a national and global resource is extremely valuable. Biological resources once lost cannot be replaced at any cost.